2016
DOI: 10.1016/j.ijggc.2016.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid fluid–structure interaction modelling of dynamic brittle fracture in steel pipelines transporting CO 2 streams

Abstract: Using the proposed model, a study is performed to evaluate the rate of brittle fracture propagation in a real-scale 48 diameter API X70 steel pipeline. The model was verified by comparing the obtained numerical results against available semi-empirical approaches from the literature. The simulated results are found to be in good correlation with the simulations using a simple semi-empirical model accounting for the fracture toughness, indicating the capability of the proposed approach to predict running brittle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Since its particular importance, it is always referred to as the artery of the national economy. Many scholars have conducted numerous studies on the mechanical properties of uncorroded pipelines [1][2][3][4]. Unfortunately, due to their aging and features of the materials, pipelines are incredibly vulnerable to external environmental erosion which may result in defects in generation and then reduce their reliability together with a series of catastrophic chain reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Since its particular importance, it is always referred to as the artery of the national economy. Many scholars have conducted numerous studies on the mechanical properties of uncorroded pipelines [1][2][3][4]. Unfortunately, due to their aging and features of the materials, pipelines are incredibly vulnerable to external environmental erosion which may result in defects in generation and then reduce their reliability together with a series of catastrophic chain reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it is worth noting that, in each of the sensitivity analyses, pipeline-based transport remains cheaper than train-based transport. Impact of impurities The impact of impurities on CO2 conditioning, transport and storage has been a sharper focus of research in the course of the past few years (Aursand et al, 2016a;Brunsvold et al, 2016;Porter et al, 2016;Rütters et al, 2016;Skaugen et al, 2016;Talemi et al, 2016). However, many evaluations Porter et al, 2016;Rütters et al, 2016;Skaugen et al, 2016) have demonstrated that the impact of impurities is very case-specific and dependent on the type and concentration of the impurities involved.…”
Section: Overall Comparisonmentioning
confidence: 99%
“…More recently, the impact of impurities in the CO2 streams on the technical design and cost performances has gained a stronger focus with especially two H2020 EU projects: IMPACTS and CO2 QUEST. In addition to providing overall recommendations regarding the evaluation of the impact of impurities on CO2 transport and storage (Brunsvold et al, 2016;Porter et al, 2016;Rütters et al, 2016;Skaugen et al, 2016), these projects addressed the impact of impurities on pipeline decompression (Aursand et al, 2016a) and fracture (Talemi et al, 2016), on the dispersion of CO2 in the case of leakage (Wareing et al, 2016), and even on CO2 injection and storage (De Dios et al, 2016;Waldmann et al, 2016;Wolf et al, 2016). Finally, while the technical and cost performances of CO2 conditioning and transport have been studied for pipeline transport, the results show that their impact is very much case-specific, depending particularly on the type and level of impurities, as well as the transport characteristics (Martynov et al, 2016;Porter et al, 2016;Skaugen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This combination would also benefit the development of predictive fluid-structure models aiding in the design of CO 2 -transport pipelines against running fractures [22,23]. For practical and computational reasons, the CO 2 flow is commonly described using a 1D model, which implies a simplified description of the pressure forces on the opening pipe flanks [22].…”
Section: Introductionmentioning
confidence: 99%